Kajian Unsur Intrinsik Dalam Komik How To Fight Karya Park Tae-Jun - Levi Al Kausar; Siti Muslimah; Ruliyani Ruliyani; Anwarsani Anwarsani; Siti Rahmawati; Nabila Salwa (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Hobin is a teenager who was initially considered weak and often became a victim of bullying at school because of his poor physical condition. Hobin's life changes began when he discovered the Newtube channel which provided fighting guides. Hobin utilizes this platform to create his personal fighting content, not only as entertainment, but also as a means of positive change in his life. His decision received a positive response, bringing significant changes to his popularity and resulting in impressive physical and mental growth. This article aims to conduct a study of the intrinsic elements of this comic, exploring aspects of character development, storyline, and moral message, especially through Hobin's journey of transformation, which creates a strong basis for an in-depth study of the comic "How To Fight" by Park Tae Jun.